2014
DOI: 10.3109/00365521.2014.978818
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gender and socioeconomic background on the decision to perform gallstone surgery: a population-based register study

Abstract: Presentations of gallstone disease differ between men and women, as does the decision to perform surgery. The higher incidence of surgery for secondary complications in older men could be explained by a higher prevalence of gallstones resulting from a lower incidence of surgery at a younger age. Whether or not wider indications for surgery in young patients reduce the risk for gallstone complications requiring surgery should be explored in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
0
12
1
1
Order By: Relevance
“…The lack of change in surgery rate in men and the decreased rate in women is explained by the fact that surgery for uncomplicated gallstone disease is more common in women compared to men. 14 Over the last decade, surgery for gallstone disease has been more common in octogenarians. 15 This is probably due to an increased life expectancy in the population as well as a lower threshold for surgery in the elderly and frail.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of change in surgery rate in men and the decreased rate in women is explained by the fact that surgery for uncomplicated gallstone disease is more common in women compared to men. 14 Over the last decade, surgery for gallstone disease has been more common in octogenarians. 15 This is probably due to an increased life expectancy in the population as well as a lower threshold for surgery in the elderly and frail.…”
Section: Discussionmentioning
confidence: 99%
“…42 Male patients were presented with more severe gallstone diseases and more frequently underwent cholecystectomy for complicated gallstones, while female patients had milder gallstone diseases and more frequently performed surgery for biliary pain. 42 Therefore, the harmful effects of complicated gallstones and risk reduction by cholecystectomy might be greater in male patients. The risk of HCC for gallstones or cholecystectomy was higher in female patients than in male patients.…”
Section: Discussionmentioning
confidence: 99%
“…The higher likelihood of undergoing arthrodesis for female patients may be supported by the notion that these decisions are based on surgeon preference, patient expectations, and cultural factors, as well as a possibly higher association of instability with LSS that might have been underestimated by ICD-9 coding. 19 The type of procedure performed for LSS in the US elderly population has been shown to differ by geographic location. 3,23 Weinstein et al 23 reported that arthrodesis rates among elderly patients were highest in many Mid- west and Southern states compared with the Northeast and the West.…”
Section: Discussionmentioning
confidence: 99%